A rumor of angels : modern society and the rediscovery of the supernatural - Berger, Peter L., 1929- (Colección de libros electrónicos de ULoyola, 1969)
Influential scholar Peter L. Berger reveals five signs that point to the supernatural and its place in a modern secular society Acclaimed scholar and sociologist Peter L. Berger examines religion in twentieth-century Western society, exploring the social nature of knowledge and its effect on religious belief. Using five signs evident in ordinary life?order, play, hope, damnation, and humor?Berger calls for a rediscovery of the supernatural as a crucial, rich dimension of humanity. Conceived as a response to his influential book The Sacred Canopy, Berger eschews technical jargon and speaks directly and systematically to those, like himself, who wish to explore religious questions.